2017
DOI: 10.5798/dicletip.298567
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Hizmetleri Meslek Yüksekokulu Öğrencilerinin Sağlıklı Yaşam Biçimi Davranışları ve Etkileyen Faktörler

Abstract: ÖzetGiriş: Bu çalışma Dicle Üniversitesi (D.Ü.) Atatürk Sağlık Hizmetleri Meslek Yüksekokulu 1.sınıfında öğrenim gören öğrencilerin sağlıklı yaşam davranışı biçimlerini belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Yöntemler: Araştırmanın evrenini Sağlık Hizmetleri Meslek Yüksekokul'u 1.sınıf öğrencileri (251 öğrenci) oluşturmaktadır. Katılımcılara demografik verileri içeren yapılandırılmış bir anket ile Walker tarafından düzenlenen ve 2008 yılında Bahar ve arkadaşları tarafından Türkçe geçerlik ve güven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 7 publications
0
3
0
9
Order By: Relevance
“…A study by Kostak et al 29 conducted with 474 university students found that the mean HLBS-II was 126.55±18.76 while a study by Yılmazel et al 30 found it to be 121.57±19.65 in nursing students. In a study conducted by Sen et al with 251 university students, the mean score of HLBS-II was found 118.0 ± 21.0 31 . According to previous studies, there were many 803 studies conducted in this area and similar results were obtained [32][33][34][35] .…”
Section: Table 4 the Comparison Of Hlbs-ii Scores Of The Interventiomentioning
confidence: 91%
“…A study by Kostak et al 29 conducted with 474 university students found that the mean HLBS-II was 126.55±18.76 while a study by Yılmazel et al 30 found it to be 121.57±19.65 in nursing students. In a study conducted by Sen et al with 251 university students, the mean score of HLBS-II was found 118.0 ± 21.0 31 . According to previous studies, there were many 803 studies conducted in this area and similar results were obtained [32][33][34][35] .…”
Section: Table 4 the Comparison Of Hlbs-ii Scores Of The Interventiomentioning
confidence: 91%
“…Nutrition, interpersonal relations and total mean score of the students with high educated mothers were significant (p<0.05). [14] In the descriptive and cross-sectional study with the aim of determining how healthy the living of 320 students are, the survey form prepared by researchers Health-Promoting Living Profile (HPLP; Walker, Sechrist & Pender, 1987) The Measurement of Coping With Stress (WCCL; Aysan, 1988Aysan, , 1994 and Beck Depression Inventory (BDI; Hisli, 1988; Şahin, 1989; Teğin, 1980) were applied. As a result of the research, it was determined that students did not have sufficient knowledge to maintain a healthy living, did not use effective methods to cope with stress, and 40% of them were depressed.…”
Section: Investigations On Healthy Living Behaviors and Related Factorsmentioning
confidence: 99%
“…İnsanları hastalıktan korumak, yaşamlarını sağlıklı olarak sürdürebilme uygulamalarının tümü sağlıklı yaşam biçimi olarak tanımlanmaktadır (Gül ve Şahin, 2019). Sağlıklı yaşam biçimi kişilerin; beslenme alışkanlıkları, sağlık sorumluluğu, egzersiz, kendini gerçekleştirme, kişilerarası destek ve stres yönetimine karşılık yapılan değerlendirmelerinin tümünü içermektedir (Cihangiroğlu ve Deveci, 2011;Kılıç ve Balta, 2019;Tambağ, 2011). Sağlıklı yaşam biçimi kişilerin yalnızca hastalıklardan korumanın yanı sıra hayatı süresince fiziksel uygunluk düzeyini geliştiren davranışları içermelidir.…”
Section: Introductionunclassified
“…Bu davranışlar kişinin fiziksel uygunluk düzeyini geliştirmenin yanı sıra kendinin fiziksel yönden olumlu yönde geliştirmeyi içermektedir. Dengeli beslenme, yeterli ve düzenli aktivite, sağlığa zararlı maddelerden kaçınma, sağlık sorumluluğu ve stresle başa çıkma davranışları kişi ve toplumların sağlığının olumlu yönde geliştirilmesini etkileyen davranışlardır (Vural ve Bakır, 2015;Beydağ vd., 2014;Altay ve ark., 2015).…”
Section: Introductionunclassified